A Lipopolysaccharide Synthesis Gene rfaD from Mesorhizobium huakuii Is Involved in Nodule Development and Symbiotic Nitrogen Fixation - Liu, Yuan; Lin, Ye; Guan, Ning; Song, Yuting; Li, Youguo; Xie, Xianan (Microorganisms (Basel), 2022)
Rhizobium lipopolysaccharide (LPS) is an important component of the cell wall of gram-negative bacteria and serves as a signal molecule on the surface of rhizobia, participating in the symbiosis during rhizobia–legume interaction. In this study, we constructed a deletion mutant of ADP-L-glycerol-D-mannoheptosyl-6-exoisomerase (rfaD) of Mesorhizobium huakuii 7653R and a functional complementary strain. The results showed that the deletion of rfaD did not affect the free-living growth rate of 7653R, but that it did affect the LPS synthesis and that it increased sensitivity to abiotic stresses. The rfaD promoter-GUS reporter assay showed that the gene was mainly expressed in the infection zone of the mature nodules. The root nodules formation of the rfaD mutant was delayed during symbiosis with the host plant of Astragalus sinicus. The symbiotic phenotype analyses showed that the nodules of A. sinicus lost symbiotic nitrogen fixation ability, when inoculated with the rfaD mutant strain. In conclusion, our results reveal that the 7653R rfaD gene plays a crucial role in the LPS synthesis involved in the symbiotic interaction between rhizobia and A. sinicus. This study also provides new insights into the molecular mechanisms by which the rhizobia regulate their own gene expression and cell wall components enabling nodulation in legumes.